2019
DOI: 10.1108/mi-05-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and applications of abrasive processes for microelectronics fabrications

Abstract: Purpose This paper aims to review recent advances and applications of abrasive processes for microelectronics fabrications. Design/methodology/approach More than 80 patents and journal and conference articles published recently are reviewed. The topics covered are chemical mechanical polishing (CMP) for semiconductor devices, key/additional process conditions for CMP, and polishing and grinding for microelectronics fabrications and fan-out wafer level packages (FOWLPs). Findings Many reviewed articles repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The fabrication-based faults need to be taken care at the time of fabrication by incorporating different testing methods such as air-to-air thermal shock testing (Tian et al, 2020). Moreover, factors such as thermal stability issues (Peng and Yam, 2019), sub-surface damage and the strength of wafers need to be put under check for increasing the reliable fabrication (Zhong, 2019) of the dies. Otherwise, low reliability or electrical conductivity test failures can render the die useless (Nadaraja and Yap, 2019).…”
Section: Proposed Algorithmmentioning
confidence: 99%
“…The fabrication-based faults need to be taken care at the time of fabrication by incorporating different testing methods such as air-to-air thermal shock testing (Tian et al, 2020). Moreover, factors such as thermal stability issues (Peng and Yam, 2019), sub-surface damage and the strength of wafers need to be put under check for increasing the reliable fabrication (Zhong, 2019) of the dies. Otherwise, low reliability or electrical conductivity test failures can render the die useless (Nadaraja and Yap, 2019).…”
Section: Proposed Algorithmmentioning
confidence: 99%
“…They found that the larger the abrasive particle size, the higher the load, with larger loads causing greater damage to friction-pair surfaces. As we are currently witnessing rapid developments in precision mechanical equipment and high-end technology, the above discussion makes it apparent that it is very important to remove nano- and micron-level abrasive particles after the running-in stage in micromechanical systems to enhance lubrication performance. This is especially true when manufacturing integrated circuits and in chemical mechanical polishing (CMP) processes, during which some abrasive particles become embedded in the surface of the film layer, which makes them difficult to remove . Ng et al explored the effect of using surfactants on surface cleaning after CMP and found that surfactants can effectively reduce the number of residual large abrasive particles attached to the surface of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Stealth dicing [17][18][19] is another state-of-the-art dicing method where a pulsed laser, at a wavelength capable of penetrating the material, is focused inside the substrate. Focused laser spots cause an extremely high power density, both temporally and spatially, at localized points.…”
Section: Introductionmentioning
confidence: 99%